Pengembangan Pendidikan Moderasi Beragama pada Usia Remaja - Haryanto, Rizki; Delon, Julian; Wahyudi, Wahyudi (Bestari, 2023)
The aim of this study is to ascertain the progress of religious moderation education among adolescents and to identify any uncertainties they may have regarding religion and religious moderation. This study employs a literature review research methodology. The book "Citizenship Education and Religious Moderation" serves as the primary data source for this research. Data was gathered via documentation studies, wherein we sought out data in the form of written records, such as notes, transcripts, books, journals, papers, articles, websites, minutes, and similar sources. The primary data sources employed are the book "Citizenship Education and Religious Moderation," scholarly journals, and documents pertaining to the advancement of religious moderation education in teenagers. The research findings indicate that there are fluctuations in the inclination of adolescents and young people to practice religious moderation, which suggests a potential decline in the values of religious moderation. To counteract this trend and promote religious moderation among adolescents, it is recommended to provide religious moderation education within the family setting and make it mandatory in the broader environment. The education of the younger generation should focus on instilling a mindset and thoughts that promote religious moderation and civilization. It is crucial for the younger generation to prioritize tolerant behavior towards other religions, both within the school environment and in the wider community. This will foster harmony and unity among different religions, leading to lasting wholeness and unity.